2019
DOI: 10.1097/tp.0000000000002543
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Outcomes of Low Physical Activity Posttransplant: A Systematic Review and Meta-Analysis

Abstract: Background. Little is known about associations between low physical activity (PA) and its correlates and outcomes in solid organ transplant recipients. This systematic review with meta-analysis examined correlates and outcomes associated with low PA (ie, not meeting individual study’s definition of being physically active) following solid organ transplantation. Methods. We searched PubMed, CINAHL, PsycINFO, and EMBASE from inception to February 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 62 publications
1
30
0
3
Order By: Relevance
“…Few studies have examined correlates of physical activity and sedentary behaviors in the solid organ transplant context. 10 Our study is one of the first to examine correlates of accelerometer-based physical activity, light intensity activity, steps, and sedentary time in kidney transplant recipients. While MVPA was inversely associated with age, steps/day was inversely associated with age and positively associated with income.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined correlates of physical activity and sedentary behaviors in the solid organ transplant context. 10 Our study is one of the first to examine correlates of accelerometer-based physical activity, light intensity activity, steps, and sedentary time in kidney transplant recipients. While MVPA was inversely associated with age, steps/day was inversely associated with age and positively associated with income.…”
Section: Discussionmentioning
confidence: 99%
“…9 Accelerometers now provide a means for more precise and, accurate estimates of sedentary time and physical activity. A recent systematic review and meta analysis by Berben and colleagues 10 examining correlates and outcomes of low physical activity post transplant reported few studies in the area of solid organ transplant recipients. These studies relied primarily on self-reported estimates of physical activity, and the authors recommended researchers should use activity monitors to document physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…35 No significant risk factors were found for low physical exercise. 36 Most of these studies are based on the results of kidney recipients, while research on heart recipients is rare. Especially studies connecting non-pharmacological NA with electronically monitored IS NA in HTRs are missing.…”
Section: Open Accessmentioning
confidence: 99%
“…15 A systematic review of low PA-related outcomes in solid organ transplantation patients showed that the predictors of low PA are older age, male sex, high BMI, a longer time since transplantation, and lower physical health-related quality of life (HRQOL). 16 HRQOL is an important outcome for patients who undergo transplantation, and a previous study showed associations between HRQOL, assessed using the short form (SF)-36 survey, and activity level 17 in post-LT patients. Physical Component Summary (PCS), but not Mental Component Summary (MCS), was associated with the level of PA, assessed using the self-reported frequency and duration of dedicated exercise, and specifically, "physical functioning," "role physical," bodily pain, general health, and PCS were associated with the PA level.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of low PA‐related outcomes in solid organ transplantation patients showed that the predictors of low PA are older age, male sex, high BMI, a longer time since transplantation, and lower physical health‐related quality of life (HRQOL) 16 …”
Section: Introductionmentioning
confidence: 99%